Pola Komunikasi Antara Pedagang dan Pembeli di Desa Pare, Kampung Inggris Kediri - Azeharie, Suzy (Jurnal Komunikasi, 2016)
Abstract This study will examine the patterns of communication used between merchants with shoppers, teachers and students, as well as in rural communities or village English Pare Kediri regency in East Java. Methodology used is a qualitative methodology with data collection through interviews, direct observation Pare village, and through the study of literature. The theories used are the theory of verbal and nonverbal communication, interpersonal communication, the theory of acculturation and assimilation of culture. The conclusion from this study is the communication patterns merchants with shoppers, teachers and students, as well as in rural communities Pare take place in the primary, which means face to face and in English. Basic English Course in operation since 1976 turned out to be a big impact in the lives of people in the village, such changes include the shift of the livelihoods of residents who are traditionally farmers have become the owner of an English language course, rent boarding houses, kiosks drinks and food, open rental bike, copy, etc. Abstrak Penelitian ini akan mengupas mengenai pola komunikasi yang digunakan antara pedagang dengan pembeli, guru dengan siswa, serta komunitas masyarakat di desa Pare atau kampung Inggris Kabupaten Kediri Jawa Timur. Metodelogi yang digunakan adalah metodologi kualitatif dengan teknik pengumpulan data melalui wawancara, observasi langsung ke desa Pare, dan melalui studi literatur. Teori-teori yang digunakan adalah teori komunikasi verbal dan non verbal, komunikasi interpersonal, teori akulturasi dan asimilasi budaya. Kesimpulan dari penelitian ini adalah pola komunikasi pedagang dengan pembeli, guru dengan siswa, serta komunitas masyarakat di desa Pare berlangsung secara primer, artinya bertatap muka dan menggunakan bahasa Inggris. Basic English Course yang beroperasi sejak tahun 1976 ternyata membawa pengaruh besar dalam kehidupan masyarakat di desa tersebut, perubahan tersebut antara lain beralihnya mata pencaharian penduduk yang secara tradisional adalah petani menjadi pemilik kursus bahasa Inggris, menyewakan rumah kos, membuka warung minuman dan makanan, membuka rental sepeda, fotocopy, dll.